2015
DOI: 10.1177/0269881114563634
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and dopamine in schizophrenia: An update for the 21st century

Abstract: The glutamate and dopamine hypotheses are leading theories of the pathoaetiology of schizophrenia. Both were initially based on indirect evidence from pharmacological studies supported by post-mortem findings, but have since been substantially advanced by new lines of evidence from in vivo imaging studies. This review provides an update on the latest findings on dopamine and glutamate abnormalities in schizophrenia, focusing on in vivo neuroimaging studies in patients and clinical high-risk groups, and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
433
0
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(475 citation statements)
references
References 266 publications
(308 reference statements)
24
433
0
18
Order By: Relevance
“…Current antipsychotics lack selective discrimination of dopamine D2 and D3 receptors, however recent positron emission tomography studies (Howes et al, 2015) show these have a differential brain distribution. The D3 receptor is abundant in the ventral striatal mesolimbic system and frontal cortex but (unlike the D2 receptor) low in the dorsal striatum, which may account for the paucity of effect of D3 antagonists on locomotor activity in rodents and provides potential for few extrapyramidal symptom in clinical use in man (see reviews; (Heidbreder and Newman, 2010; Millan and Brocco, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current antipsychotics lack selective discrimination of dopamine D2 and D3 receptors, however recent positron emission tomography studies (Howes et al, 2015) show these have a differential brain distribution. The D3 receptor is abundant in the ventral striatal mesolimbic system and frontal cortex but (unlike the D2 receptor) low in the dorsal striatum, which may account for the paucity of effect of D3 antagonists on locomotor activity in rodents and provides potential for few extrapyramidal symptom in clinical use in man (see reviews; (Heidbreder and Newman, 2010; Millan and Brocco, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Second generation atypical antipsychotics were developed in an attempt to improve therapy but still have limited effect on cognitive deficits or negative symptoms and many cause weight gain and metabolic abnormalities (Miyamoto et al, 2012). Thus new therapeutic agents operating through different pharmacological mechanisms are essential for more effective management of schizophrenia.One potential mechanism, preferential targeting of the dopamine D3 receptor over the dopamine D2 receptor, might provide effective relief of positive and negative symptoms combined with improved cognitive function (Gyertyán et al, 2008; Laszy et al, 2005; Millan and Brocco, 2008; Millan et al, 2008).Current antipsychotics lack selective discrimination of dopamine D2 and D3 receptors, however recent positron emission tomography studies (Howes et al, 2015) show these have a differential brain distribution. The D3 receptor is abundant in the ventral striatal mesolimbic system and frontal cortex but (unlike the D2 receptor) low in the dorsal striatum, which may account for the paucity of effect of D3 antagonists on locomotor activity in rodents and provides potential for few extrapyramidal symptom in clinical use in man (see reviews; (Heidbreder and Newman, 2010; Millan and Brocco, 2008).…”
mentioning
confidence: 99%
“…Two of the most influential hypotheses concerning the underlying neurobiology of the disorder involve dopamine and glutamate [11]. The first evidence supporting these hypotheses goes back to the 1970s originating from in vitro studies on dopamine receptors and antipsychotics.…”
Section: Neurochemical Biomarkersmentioning
confidence: 99%
“…In the last decade, considerable research efforts revealed a vast array of chemical [11] functional [12] and structural brain abnormalities [13] that may constitute the 'organic surrogate' of the illness [14]. The field of neuroimaging leveraged unprecedented insight into brain biology, showing promising progress towards the identification of putative biomarkers, which could be used for early diagnosis, treatment planning, and monitoring of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The dopamine hypothesis, based on evidence from pharmacological and in vivo imaging studies, is considered the final common pathway for psychotic symptoms in schizophrenia. 8 The enzyme catechol-O-methyltransferase (COMT) metabolizes several catecholamines, but is especially relevant to dopaminergic transmission in the prefrontal cortex (PFC), in which it is a key element to dopamine availability. 9 COMT is encoded by a single gene (also COMT) located on chromosome 22q11.2, a region that is commonly missing in 22q11.2 microdeletion syndrome, which has long been associated with predisposition for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%